The degree to which Quality Matters standards are met in the "Madrasati Platform" e-learning management system from the perspective of secondary - Alanazi, Majida Abdullah; Alqahtani, Nada Nasser (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to identify the degree to which Quality Matters standards are met in the electronic learning management system "Madrasati Platform" from the perspective of secondary school teachers. It also aimed to investigate whether there are statistically significant differences in the responses of the study sample regarding the degree to which Quality Matters standards are met in the "Madrasati Platform" electronic learning management system, attributed to the variables of training courses and gender. To achieve the study objectives, a descriptive survey method was used. The study sample consisted of (138) male and female secondary school teachers in Riyadh, Saudi Arabia. A questionnaire was used as a data collection tool. The results showed a (high) degree of availability with a weighted mean of (3.8) and a relative weight of (76), and there were statistically significant differences between the mean scores of the study sample’s responses regarding the degree to which Quality Matters standards are met in the "Madrasati Platform" electronic learning management system, attributed to the variable of training courses, in favor of the group that received training, and there were no statistically significant differences between the mean scores of the study sample’s responses regarding the degree to which Quality Matters standards are met in the "Madrasati Platform" electronic learning management system, attributed to the gender variable, on all axes.